2022
DOI: 10.1371/journal.pone.0278962
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of human amygdala nuclei to resting-state networks

Abstract: The amygdala is a brain region with a complex internal structure that is associated with psychiatric disease. Methodological limitations have complicated the study of the internal structure of the amygdala in humans. In the current study we examined the functional connectivity between nine amygdaloid nuclei and existing resting-state networks using a high spatial-resolution fMRI dataset. Using data-driven analysis techniques we found that there were three main clusters inside the amygdala that correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Our study identified a cluster of reduced functional connectivity in the left hippocampus, amygdala and parahippocampal gyrus, as well as the connectivity and convergence of this cluster with the default mode network. This finding resonates with previous findings of reduced functional connectivity in the default mode network in Alzheimer’s disease, 48 and particularly a left-sided alteration in its posterior subnetwork, 102 and with findings of the connectivity between these medial temporal lobe regions and the default mode network 29 , 82-84 , 103 (with exceptions 104 ). These findings mirror broader pathology associations with the cortical default mode network 40 , 105 and also align with a recently proposed model of Alzheimer’s disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study identified a cluster of reduced functional connectivity in the left hippocampus, amygdala and parahippocampal gyrus, as well as the connectivity and convergence of this cluster with the default mode network. This finding resonates with previous findings of reduced functional connectivity in the default mode network in Alzheimer’s disease, 48 and particularly a left-sided alteration in its posterior subnetwork, 102 and with findings of the connectivity between these medial temporal lobe regions and the default mode network 29 , 82-84 , 103 (with exceptions 104 ). These findings mirror broader pathology associations with the cortical default mode network 40 , 105 and also align with a recently proposed model of Alzheimer’s disease.…”
Section: Discussionsupporting
confidence: 91%
“… 81 Considering this variability and the resolution of the results from this meta-analysis, the specific contributions within the thalamus remain unclear. Brain areas within the cortical default mode network also coactivate with the amygdala 29 , 82-84 (with laterobasal, superficial and centromedial nuclei) and the cerebellum (CrusI/II and lobule and vermis IX, with some reports on lobules VIIIB and X). 30 , 76 , 85-87 …”
Section: Discussionmentioning
confidence: 98%
“…Brain areas within the cortical default mode network coactivate with the amygdala [27,66] and the cerebellum [28,60,67,68]. The coactivation with the amygdala involves variable groups of nuclei, including nuclei in the laterobasal, superficial, and centromedial areas [27,66,69,70]. The coactivation with the cerebellum has mainly involved the CrusI/II and lobule and vermis IX of the cerebellum [19,28,60,67,68,71], although lobules VIIIB and X have also been identified [60,71].…”
Section: Discussionmentioning
confidence: 99%
“…Given the variability in previous research and the resolution of the results from this meta-analysis, it remains impossible to clarify the specific contributions within the thalamus. Brain areas within the cortical default mode network coactivate with the amygdala [27, 66] and the cerebellum [28, 60, 67, 68]. The coactivation with the amygdala involves variable groups of nuclei, including nuclei in the laterobasal, superficial, and centromedial areas [27, 66, 69, 70].…”
Section: Discussionmentioning
confidence: 99%
“…These findings could be a foundation for the development of clinical practice image biomarkers. On the other hand, specific configurations of the different amygdaloid nuclei with certain resting-state networks using a high spatial-resolution fMRI dataset have demonstrated that amygdaloid connectivity is not confined to traditional large-scale divisions (Elvira et al, 2022). Also, the utilization of high-resolution structural images to allow consistent segmentations of the amygdala into their constituent substructures may offer some control over investigator bias (Brown et al, 2019).…”
Section: Future Perspectivesmentioning
confidence: 99%